Optimization of exposure parameters in full field digital mammography using figure of merit - Laila Suryani Elias,; Eng, May Lin; Ang, Wee Chin; Abd Aziz Tajuddin,; Shantini A. Arasaratnam,; Suraya Aziz,; Khairul Osman,; Kanaga Kumari Chelliah, (Universiti Kebangsaan Malaysia, 2010)
Mammography is used as a screening tool for early detection of breast cancer. However, the radiation dose used should be as low as possible to minimize any effects on asymptomatic woman while maintaining the diagnostic value of the image as mammography is done annually. This study was done to determine the optimum exposure parameter in exposure control mode (AEC) for two combinations of anode/filter which were molybdenum/molybdenum (Mo/Mo) and molybdenum/rhodium (Mo/Rh) using the Lorad Selenia digital mammography system at the Women’s Breast Clinic, National Cancer Society (NCS). A CIRS012A mammography research of phantom 4 cm thickness with 50% glandularity was exposed in the cranio-caudal projection. TLD 100H was used to measure the entrance surface air kerma (ESAK). The AGD values were then calculated from the ESAK values, incorporating three correction factors (g, c and s) according to Euref protocol. Image quality was evaluated using signal to noise ratio (SNR). Figure of Merit (FOM) which is the ratio of the square of SNR to the AGD shows that 30 kVp is the optimum exposure parameter for a 4 cm thickness phantom with the use of Mo/Rh and Mo/Mo anode/filter combination. Non-parametric Spearman correlation test showed a negative linear relationship between AGD and SNR with increasing tube voltage for both anode/filters.